The Legacy of Lerdahl and Jackendoff’s A Generative Theory of Tonal Music : Bridging a significant event in the history of music theory and recent developments in cognitive music research - Hansen, Niels Chr. (Danish Yearbook of Musicology, 2011)
Fred Lerdahl and Ray Jackendoff’s A Generative Theory of Tonal Music (GTTM) has only received limited attention in Danish music theory. Yet, its influence is irrefutable in terms of introducing the ‘cognitive paradigm’, which changed analytical focus from musical structure to the listening process. Recently, music cognition research has gained territory in Denmark, thus warranting a re-assessment of GTTM and its legacy. This paper provides an overview of GTTM outlining typical points of criticism. These include a simplified view on music, an unresolved conflict between global and local listening, an occasionally underspecified rule system, and unsubstantiated claims of universality and innateness based on intuition rather than cross-cultural research. GTTM’s reception and legacy is discussed in terms of 1) empirical testing, 2) theoretical refinement, 3) rule quantification, 4) computational implementation, and 5) application. Empirical findings have repeatedly emphasized the significance of surface structure and non-hierarchical, real-time listening, and models acquiring knowledge through unsupervised, statistical learning have largely replaced rule-based ones in cognitive modelling. This allows researchers to account for cultural differences, which Lerdahl and Jackendoff were strongly ambiguous about. Moreover, GTTM has not been widely acknowledged by analysts, is hardly included in the theory curriculum, and is primarily cited by present-day theorists to justify simple claims about hierarchical organization. Nevertheless, GTTM was instrumental in establishing a link between music theory and psychology, which has encouraged empirical research with music-theoretical implications within the fi elds of music cognition, experimental psychology, computational modelling, and cognitive neuroscience.